Capitalism and collapse of humanity: A study of The Great Gatsby and Seize the Day - Alam, Md Morshedul; Ahmad, Shamim (IIUC Studies, 2022)
Disregard for men by men for money and wealth prompted by capitalism plays a devastating role in modern societies. In The Great Gatsby (1925) and Seize the Day (1956) by F. Scott Fitzgerald and Saul Bellow respectively, the two American novelists portray a modern society of America belonging to 1920’s and 1950’s, which fosters capitalism to bring disaster to human life. More specifically, Tom Buchanan in The Great Gatsby and Dr. Adler in Seize the Day have involved in manifold activities destructive to human relationship stirred up by material success which significantly exposes them as a capitalist. They prove themselves neither to be truly moral nor pro-human so, they possess the negative qualities of the capitalist victimizers of men. This paper attempts to explore how Tom Buchanan and Dr. Adler, representing two different decades of twentieth century capitalistic America, nurture the objective of earning money and wealth, perform anti-human activities and turn capitalist victimizers. For this kind of human nature, ultimately, men collapse and consequently, individuals, family and society go through inhuman sufferings. IIUC Studies Vol.18, December 2021: 123-134